Correlation between Neutrophil-Lymphocyte Ratio and Urea Serum in Hemodialysis Patients at Dr. Doris Sylvanus Hospital - Nafisy Apritis Sambo; Lia Sasmithae; Sintha Nugrahini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Chronic Kidney Disease (CKD) is a condition characterized by kidney damage for > 3 months, as well as structural or functional abnormalities with or without a decrease in Glomerular Filtration Rate (GFR) < 60 mL/minute/1.73. This damage leads to increased urea levels in the blood, also known as uremia, which can increase the risk of inflammation in CKD patients undergoing hemodialysis (HD). Previous studies revealed that increased urea and Neutrophil-Lymphocyte Ratio (NLR) can be used as inflammatory biomarkers to replace CRP, IL-6, and other indicators. This study aimed to determine the correlation between NLR and serum urea levels in pre- and post-HD CKD patients at Dr. Doris Sylvanus Hospital. An analytical survey method was used with a retrospective design.The process started by taking medical records of patients currently undergoing HD who were selected as respondents. The sample population consisted of 50 (70.4%) males and 21 (29.6%) females. Based on the age group, 43.7% of patients were aged 51-60. The results showed that the average NLR pre- and post-HD were 5.24±4.88 and 10.41±12.31, respectively. The average urea pre- and post-HD were 195.97±77.88 and 120.97±47.4, respectively. The bivariate analysis showed a significant weak correlation between NLR and serum urea level pre-HD (p=0.004 with r =0.338) and post-HD (p=0.039 with r =0.246) in patients.